FILTRATION SURGERY OF TRABECTULECTOMIES WITH 5 – FLUOROURACIL IN ADVANCED POAG: Poster Presentation - Case Report - Resident - Fidalia; Amrina, Fadillah; Sari, Prima Maya (Majalah Oftalmologi Indonesia, 2023)
Introduction : Advanced Glaucoma (AG) is total cupping of optic nerve with or without severe visual field loss. The prevalence of AG in POAG, shows that 15% have a substantial visual field defect. Initial therapy for AG can use medications, surgical therapy is performed when adecuate medical treatment isn’t effective. Filtration surgery such as trabeculectomy and implantation of tube shunts can be performed. This case reports aims to understand the used of trabeculectomy+5FU in Advanced POAG. Case Illustration : A 55 years old woman came with blurry and tunnel vision accompanied by headache since 2 years ago. She got treatment yet stopped to control. Vision has progressively reduced since 2 months ago. Visual acuity OD 1/300 OS 1/60, IOP OD 25.1 mmHg and OS 29.8 mmHg with 4 drugs, cloudy lens, cupping, c/d ratio 0.9, nasalization, bayonet sign and peripapillary atrophy. The patient was diagnosed with Advanced POAG with immature senile cataract ODS. Patient was treated with trabeculectomy+5-FU due to uncontrolled IOP despite receiving adecuate therapy. Releasing sutures were used to control IOP after surgery. After surgery, the last IOP OS 12.6 mmHg, and bleb formed E1H1V0. Discussion : Conclusion : Patients was treated with trabeculectomy+5-FU, can control IOP stably in advance of POAG without serious complications, cost less than routine drugs and maintain visual function and improve quality of life. Filtration surgery such as trabeculectomy with AF agents is proven to reduce IOP more stably in advance of POAG.